Макромоделі амплітудно- та частотнонезалежного помножувача частоти гармонічних сигналів - Тимощук, П. В. (Видавництво Національного університету «Львівська політехніка», 2001)
The amplitude and frequency independent analogue and discrete macromodels of harmonic signals frequency multiplier on three has been built. The analogue macromodel has been designed in the rational function form with the influences and their integrals as the arguments. The discrete macromodel has been obtained in the appropriate discrete equation aspect.